I know why the caged bird sings - Angelou, Maya. (New York : Bantam Books, 1993)
Presents the story of a spirited and gifted, but poor, Black girl growing up in the South in the 1930's. Tells how she came into her own, experiencing prejudice, family difficulties, and a relationship with a teacher who taught her to respect books, learning, and herself.
"Bantam edition / March 1971"--t.p. verso.
Autobiography
Large print.
Keywords: Angelou, Maya; Authors, American -- 20th century -- Biography